THE RELATIONSHIP BETWEEN LEADERSHIP AND VILLAGE PERFORMANCE AND SUSTAINABILITY IN HIGH-POVERTY AREAS IN SUMATRA - Fachruzzaman; Rini Indriani; Amanda Alvi Nurdiantoro (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2026)
The Village Law has been in effect in Indonesia for a decade, having a positive impact on village development and governance. These achievements serve as a foundation for the government to improve future village governance and sustainability. Therefore, this study aims to investigate the relationship between leadership and village performance and sustainability in poor areas of Sumatra. This study used a quantitative approach with a survey method. Primary data were collected using questionnaires distributed to village officials and village leaders in Bengkulu and Nanggroe Aceh Darussalam Provinces. The results indicate that leadership is crucial for improving performance and achieving sustainable village development.